A mutation in Site‐1 Protease is associated with a complex phenotype that includes episodic hyperCKemia and focal myoedema. Issue 7 (8th May 2019) - Schweitzer, George G.; Gan, Connie; Bucelli, Robert C.; Wegner, Daniel; Schmidt, Robert E.; Shinawi, Marwan; Finck, Brian N.; Brookheart, Rita T.
Abstract: Background: Site‐1 Protease (S1P) is a Golgi‐resident protein required for the activation of regulatory proteins that drive key cellular functions, including, the unfolded protein response (UPR) and lipid and cholesterol biosynthesis. While disruptions in S1P function have been widely characterized in animal models, to date, the implications of disrupted S1P function in human disease states are not completely known. Methods: The patient and both parents underwent whole exome and mitochondrial DNA sequencing, and Sanger sequencing was used to confirm the mutation. Western blotting and immunofluorescence studies were performed on either proband‐derived fibroblasts or on an established cell line to assess protein expression and cellular localization of the mutated S1P protein. Quantitative real‐time PCR and luciferase reporter assays were used to examine activation of S1P target pathways in the context of the S1P mutation. Results: We describe a female patient with a de novo heterozygous missense mutation in the transmembrane domain of S1P (p. Pro1003Ser). The patient presented to our neuromuscular clinic with episodic, activity‐induced, focal myoedema and myalgias with hyperCKemia. Her clinical phenotype was complex and included gastrointestinal hypomotility, ocular migraines, and polycystic ovary syndrome. Molecular analysis using proband‐derived fibroblasts and cell lines harboring the Pro1003Ser mutation demonstrated increased activation of UPR and lipid and cholesterol regulatory pathways and localization of S1P Pro1003Ser in the Golgi. Conclusion: These findings suggest a critical function for S1P in several human organ systems and implicate an important role for S1P in various human disease states. Abstract : A de novo heterozygous mutation in Site‐1 Protease confers a gain‐of‐function effect that is associated with a complex phenotype that includes hyperCKemia, focal myoedema, and polycystic ovary syndrome.